Internationalization of SMEs: SLR (Systematic Literature Review) - Dwi Hernanik, Nova; Sudarmiatin, Sudarmiatin; Sumarsono, Hadi (Publisher Cv. Inara, 2023)
This article aims to provide a systematic review of the literature on the current state of research on highly diverse and collaborative and internationalization of small and medium enterprises (SMEs). We analyze the processes that affect the internationalization of SMEs. Additionally, highlighting the limitations of the literature, especially in terms of theoretical fragmentation; existing theories are deployed and illustrated but are rarely extended in a way that significantly informs subsequent work. With this, we highlight the need for a more rigorous and empirically informed exploration of contextual effects that considers the consequences of development in global economic ecosystems. From the results of a review of several literatures, it shows that there is an internationalization theory that tries to analyze, process, and produce results. Because in the era of globalization, small and medium companies see internationalization activities as a great opportunity to progress and develop.